UPAYA PENINGKATAN WAWASAN WARGA KP GUHA KULON MELALUI PELATIHAN INSTALASI LISTRIK - Dwiyaniti, Murie; Aji, A Damar; Nadhiroh, Nuha; Indrayani, Septina (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2020)
The residents of Kp Guha Kulon, Leuwikaret Village, Klapanunggal Subdistrict, Bogor district, consist of 233 families whose livelihoods are mostly daily laborers and traders. With the conditions of the Covid-19 pandemic, lots of residents do not work. In order to provide beneficial free time for them, the Study Program of Industrial Electrical Automation Engineering conducted a residential electrical installation training program. The purpose of this is to provide proper understanding on how to install the electricity correctly and the dangers caused by electricity. After the training, the participants were expected to have confidence in repairing or installing electricity in their houses. Apart from this program,Â  the Industrial Electrical Automation Engineering Study Program also donated 100 basic food packages to the residents. The method used in this community service consists of three parts: making training modules, conducting the training, and distributing basic necessities. The results show that all activities had run well where training modules had been given to the participants, the training had been conducted, and the basic food packages had been distributed to the residents of Kp Guha Kulon. This is proven by the enthusiasm of villagers who participated in the activities and hoped to continue for a certified training where they can be professional electricians so they can earn more income.